Analysis of Students' Mathematical Communication Abilities in Terms of Interpersonal Intelligence in Statistics Material - Siti Rohmah; Nurhayati; Rosmaiyadi (PT FORMOSA CENDEKIA GLOBAL, 2024)
This study aims to describe students' mathematical communication abilities in terms of interpersonal intelligence in the topic of statistics at SMP Negeri 20 Singkawang. This research used a qualitative descriptive approach. Data collection techniques involve tests and interviews. The results indicate that: 1) Students with high interpersonal intelligence tend to have good mathematical communication abilities, with an average score of 69.45. 2) Students with moderate interpersonal intelligence tend to have reasonably good mathematical communication abilities, with an average score of 44.95. 3) Students with low interpersonal intelligence tend to have moderately good mathematical communication abilities, with an average score of 46.67 on various indicators of mathematical communication proficiency